2021
DOI: 10.1051/0004-6361/202141351
|View full text |Cite
|
Sign up to set email alerts
|

The HARPS search for southern extra-solar planets

Abstract: Context. We present precise radial-velocity measurements of five solar-type stars observed with the HARPS Echelle spectrograph mounted on the 3.6-m telescope in La Silla (ESO, Chile). With a time span of more than 10 yr and a fairly dense sampling, the survey is sensitive to low mass planets down to super-Earths on orbital periods up to 100 days. Aims. Our goal was to search for planetary companions around the stars HD 39194, HD 93385, HD 96700, HD 154088, and HD 189567 and use Bayesian model comparison to mak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Without the context of hosting an S-type planet, DMPP-3AB is not a particularly close binary, but it is the most compact binary system to harbour an S-type planet observed thus far. It is also one of the few systems containing a radial velocity (RV) detected S-type super-Earth around an FGK star (B20; Unger et al 2021;Barros et al 2022). Su et al (2021) compare the known S-type RV discoveries, and show that DMPP-3A b is an extreme outlier in their sample.…”
Section: Introductionmentioning
confidence: 98%
“…Without the context of hosting an S-type planet, DMPP-3AB is not a particularly close binary, but it is the most compact binary system to harbour an S-type planet observed thus far. It is also one of the few systems containing a radial velocity (RV) detected S-type super-Earth around an FGK star (B20; Unger et al 2021;Barros et al 2022). Su et al (2021) compare the known S-type RV discoveries, and show that DMPP-3A b is an extreme outlier in their sample.…”
Section: Introductionmentioning
confidence: 98%
“…A significant number of detections later suggested that these planets are among the most abundant in the exoplanet population (e.g. Mayor et al 2011;Lovis et al 2011;Lo Curto et al 2013;Bonfils et al 2013;Astudillo-Defru et al 2017b;Delisle et al 2018;Unger et al 2021). Their over-abundance was strengthened by the Kepler space telescope, which scrutinised a small area of the North sky for 3.5 yr in search for transiting planets (Latham et al 2011;Borucki et al 2011;Fabrycky et al 2014).…”
Section: Introductionmentioning
confidence: 99%